A novel aryl acylamidase from Nocardia farcinica hydrolyses polyamide - Heumann, Sonja (2009)
An alkali stable polyamidase was isolated from a new strain of Nocardia farcinica. The enzyme consists of four subunits with a total molecular weight of 190 kDa. The polyamidase cleaved amide and ester bonds of water insoluble model substrates like adipic acid bishexylamide and bis(benzoyloxyethyl)terephthalate and hydrolyzed different soluble amides to the corresponding acid. Treatment of polyamide 6 with this amidase led to an increased hydrophilicity based on rising height and tensiometry measurements and evidence of surface hydrolysis of polyamide 6 is shown. In addition to amidase activity, the enzyme showed activity on p-nitrophenylbutyrate. On hexanoamide the amidase exhibited a Km value of 5.5 mM compared to 0.07 mM for p-nitroacetanilide. The polyamidase belongs to the amidase signature family and is closely related to aryl acylamidases from different strains/species of Nocardia and to the 6-aminohexanoate-cyclic dimer hydrolase (EI) from Arthrobacter sp. KI72.